Dampak Pemakaian Gadget Terhadap Kelainan Refraksi di SMPN 2 Batang Anai Padang Pariaman - Wesnita, Alvia; Amril, Alwa Pascaselnofra (Jurnal Penelitian Dan Pengkajian Ilmiah Eksakta, 2025)
This study discusses the impact of gadget usage on refractive errors among students at SMPN 2 Batang Anai, Padang Pariaman. The aim of this research is to determine the level of gadget usage among students of SMPN 2 in Batang Anai District and to analyze the extent to which gadget usage contributes to refractive errors. Data were collected through interviews, questionnaires, and visual acuity measurements conducted on students at SMPN 2 Batang Anai. The findings were then discussed based on theoretical frameworks and data analysis derived from respondents' answers. Based on data analysis involving 64 respondents, the results showed that high levels of gadget usage accounted for 89.1%, while moderate levels were at 10.9%. The refractive errors associated with gadget usage included myopia (95.3%), hyperopia (1.6%), and astigmatism (3.1%).